Genetic, genomic and systems biology analysis of adaptive evolution of budding yeast to the deletion of essential genes - Liu, Gaowen (2016)
Essential and non-essential genes are classified based on the viability of the corresponding deletion mutant cells. However previous studies in budding yeast challenged this view by showing that mutants deleted of essential or non-essential genes are capable of accumulating compensatory mutations and resume viability, suggesting that essentiality is not an intrinsic gene property but depends on the cellular capacity to evolve. To identify essential genes the lethality of which could be bypassed by short-term evolutionary processes, a four-layered screen was performed on all previously dubbed essential genes (1106). We identified 88 of such genes and dubbed as evolvable. While DNA content analysis of mutants deleted of evolvable genes showed accumulation of large-scale genome changes, short-term evolutionary experiments indicated that majority of mutants improved growth rate upon passaging, suggesting that by accumulating compensatory mutations cells evolved to the gene deletion. Network feature and conservation analyses showed that evolvable genes tend to have intermediate properties in respect to non-essential and the other essential genes, suggesting gene essentiality form a gradient. Moreover, evolvable genes were enriched in protein complexes involved in intracellular trafficking of proteins. Interestingly independently generated mutant strains carry the same gene deletion or deletion of genes involved in the same protein complex carried specific set of aneuploidies, suggesting that aneuploidy could function as an adaptive mutations and that cells respond to inactivation of different component of the same functional submodule in similar ways. Accordingly we showed that the presence of either specific aneuploidies or a specific gene on the aneuploid chromosome was required and sufficient to bypass the lethality of genes belonging to the same functional module. Dissection of the molecular mechanism at the basis of the adaptation showed that cells bypassed the crippled function not by fixing the broken machinery but by tinkering with pre-existing components and using them for novel tasks. Taken together our results suggest that essentiality form a continuum of characteristic at the gene and network-specific properties. Moreover, cellular systems respond to depletion different components of a given functional complex using similar evolutionary strategies that are brought about by whole-chromosome aneuploidy.